Rainier, the mountain [videorecording (DVD)] (KCTS, 1999)
Looks at the history of the mountain with respect to its being a challenge for mountain climbers, and rescuers. The Native American traditions about the mountain and its advertising career are discussed. The use of Rainier for training ski troops, and the CCC work there are important parts of its history. The feelings it inspires in residents and casual visitors alike sum up the value of this particular national park.